Japan as a middle power - Kobayashi, Takeshi (AUC Knowledge Fountain, 2015)

(untitled)
The main question of the proposed thesis is: what was the guiding principle of Japanese diplomacy during the Asian Financial Crisis (AFC) in the late 1990s and how did this principle help the countries in the region restore the Asian economy? My argument is that Japan responded to the Asian Financial Crisis as a middle power country and mediated opposing interests between Asia and the United States in order to stabilize the highly damaged Asian economy and prevent a recurrence of another crisis. Since the end of the Second World War, the United States led many countries in the free world by helping devastated nations, intentionally taking on more financial burden and using international institutions such as the IMF. On the other hand, demolished states such as West Germany and Japan enjoyed privilege to focus on economic reconstruction. Overall, a large number of countries became increasingly wealthier under Pax Americana. However, the US economic supremacy gradually declined inversely proportional to the rapid growth of recovering nations, benefiting from the US hegemony. In addition, more and more developing economies participated in international regimes. In order to reflect those new comers, a new concept was created as well as some actors in the Hegemonic Stability Theory, which is the middle power. A middle power is an actor, which leads others as a facilitator and relatively stronger; but, cannot compete with great powers. As the middle power initiates and represents a coalition of willing in negotiation, it is required to arrange interests fairly among the members and with the hegemon, in other words, the United States. It is possible for the middle power to restrain and modify behaviors of the hegemonic power by taking advantage of collective bargaining power. However, it does not mean that the middle power rejects cooperation with the hegemon because it needs the strongest country to achieve the goal of the group and its success depends on the stability of the economic status quo. In order to argue that Japan was a middle power during the crisis, I demonstrate that Australian developed middle power diplomacy during the GATT Uruguay Round; but was not successful enough because it was not persistently fair between the United States and the European Community. I affirm that Japan played a role of middle power even though Japan failed to get its original plan supported to establish Asian Monetary Fund in the early stage of the Asian Financial Crisis. Japan was force to withdraw the plan after it was rejected but the retreat was just a tactical error. As a result of a series of initiatives as a whole package, Japan turned the misfortune into a blessing. The country worked together with the United States and utilized a new framework, ASEAN plus Three.